Uniaxial tensile deformation behaviour of electron beam welded commercially pure titanium and Ti6Al4V joints: Experimental and metallurgical characterization. (April 2022) - Lin Prakash, P.S.; Rakshit, Rahul; Mandal, Sumantra; Roy, Gour Gopal; Panda, Sushanta Kumar
Abstract: The deformation behaviour of electron beam welded commercially pure (CP) Ti and Ti6Al4V joints have been investigated by conducting uniaxial tensile tests. The fusion zone (FZ) consists of low strained needle-like α′ martensite with four axis/angle misorientation peaks which are associated with the formation of certain crystallographic variants of α phase during cooling. The microhardness of the FZ is higher than the CP Ti owing to the presence of α′ martensite and higher volume concentration of alloying elements (Al and V) across the weld. During uniaxial tensile deformation, the failure occurs in the CP Ti side of the welded specimen due to preferential plastic deformation, which is further confirmed by the electron backscatter diffraction (EBSD) analysis. The deformed microstructure of CP Ti is characterized by the formation of 10 1 ¯ 2 10 1 ¯ 1 ¯ extension twins (ET) and 11 2 ¯ 2 11 2 ¯ 3 ¯ compression twins (CT), which lead to the grain fragmentation and subsequent formation of heterogeneous microstructure. Furthermore, the effect of uniaxial tensile loading on the evolution of microstructure and microtexture has been explored through Schmid factor (SF) analysis, performed on basal 0001 11 2 ¯ 0, prismatic 10 1 ¯ 0 11 2 ¯ 0 and pyramidal 10 1 ¯ 1 11 2 ¯ 0 slip systems. The SF analysis reveals that initially, prismatic slip systems played a dominant role during uniaxial deformation owing to their high number fraction of high SF. However, the lack of five independent slip systems to incorporate the induced strain has resulted in the activation of basal slip and the formation of CT and ET twins during deformation. Moreover, the high number fraction of low SF of basal slip system is attributed to the lowering of basal spilt angle in the micro-texture of deformed CP Ti. Graphical abstract: Unlabelled Image Highlights: Dissimilar CP Ti and Ti6Al4V butt joints were fabricated by electron beam welding. FZ consists of α′ martensite evolved through variant selection mechanism. Failure occurred in CP Ti side of weld tensile specimen. Grain fragmentation in CP Ti due to formation of extension and compression twins. Decrease in split basal angle is related to activation of basal slip system.